Persistent genital arousal disorder: always look beyond the surface - a case report - Sarabando, Rita; Sousa, Natacha; Borges, Ana C.; Nogueira-Silva, Cristina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Persistent genital arousal disorder is a rare condition characterized by unwanted intrusive symptoms of sexual arousal without specific context. Their possible aetiologies and treatments are multiple and mostly based on case reports. We aim to do a comprehensive review of persistent genital arousal disorder and describe a case of a postmenopausal woman who developed this disease and, during the follow-up, was diagnosed with advanced endometrial cancer, reminding physicians to keep in mind the possibility of multiple diagnosis in the same patient, including malignancy. Although there is no description of this association in the literature, the possible aetiologies of persistent genital arousal disorder are diverse, and we sought this rare case should be disclosed.